DOA Estimation by Fourth-Order Cumulants without Source Enumeration and Eigendecomposition - Elhafiz Abdalla Bakhit Yagoup; Zhiwen Liu; Yougen Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A new algorithm for direction of arrival (DOA) estimation is proposed.Using fourth-order cumulants and modified MUSIC (MUliplle SIgnal Classification) algorithm. However, it does not require any eigendecomposition of the cumulant matrix of the received data and source enumeration. It also eliminates the need for knowledge of the spatial characteristics of the noise and interference. This method only uses the conjugate spatial signal of different sensor positions. Computer simulation results are provided to demonstrate the performance of the proposed approach and compare them to DCI (Diagonally-loaded Conjugate correlation matrix Inverse power) method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.4679